Competitive advantage for a bank that opens itself to Virtual Currency businesses – game theory - Bok, Martin; Jedlinský, Jakub; Valík, Lubomír; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
This thesis aspires to analyze the issue of underbanking virtual currency businesses (VCBs) around the world from both the banks’ perspective and the VCB perspective and attempts to conclude, if there can be a competitive advantage for any bank that decides to start banking VCBs. The thesis is divided into 4 chapters. The first chapter is dedicated to the current situation of banking VCBs around the world. It serves as an introduction to the topic and defines the main issues causing the reluctance of banks to accept VCBs as customers. The second chapter compares the situation of VCBs with the cannabis industry that has faced similar scrutiny until recently. The third chapter is dedicated to a game theory model that is used to calculate the potential competitive advantage a bank could gain on the market. The last chapter focuses on the market in the Czech Republic to find out if any Czech bank could profit from opening itself to the VCBs. The results of the thesis suggest that a competitive advantage can exist but it is unwise for any bank to start accepting VCB customers unless they made the necessary preparations. The situation in the Czech Republic suggests that three banks have already separated themselves from the rest and are banking VCBs, while the other banks mostly avoid them.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses